Host Phylogeny and Diet Shape Gut Microbial Communities Within Bamboo-Feeding Insects - Huang, Kuanguan; Wang, Jie; Huang, Junhao; Zhang, Shouke; Vogler, Alfried P.; Liu, Quanquan; Li, Yongchun; Yang, Maowei; Li, You; Zhou, Xuguo (Frontiers in Microbiology, 2021)
Gut microbiome plays an important role in host’s development and adaption to its dietary niche. In this study, a group of bamboo-feeding insects are used to explore the potential role of gut microbiota in the convergent adaptation to extreme diet specialization. Specifically, using a 16S rRNA marker and an Illumina sequencing platform, we profiled the microbial communities of 76 gut samples collected from nine bamboo-feeding insects, including both hemimetabolous (Orthoptera and Hemiptera) and holometabolous (Coleoptera and Lepidoptera) species, which are specialized in three distinct dietary niches, bamboo leaf, shoot, and sap. The gut microbiota of these insects were dominated by Proteobacteria, Firmicutes and Bacteroidetes, and were clustered into solid (leaf and shoot) and liquid (sap) dietary niches. The gut bacteria communities of insects feeding on solid-diet overlapped significantly, even though these insects belong to phylogenetically distant lineages representing different orders. In addition, the presence of cellulolytic bacterial communities within gut microbiota allow bamboo-feeding insects to adapt to a highly specialized, fiber-rich diet. Although both phylogeny and diet can impact the structure and composition of gut microbiomes, phylogeny is the primary driving force underlying the convergent adaptation to a highly specialized diet, especially when the related insect species harbor similar gut microbiomes and share the same dietary niche over evolutionary timescales. These combined findings lay the foundation for future research on how convergent feeding strategies impact the interplays between hosts and their gut microbiomes, and how gut microbiota may facilitate convergent evolution in phylogenetically distant species in adaptation to the shared diet.